La Notion Du Pouvoir Dans Les Institutions De Gestion De Conflits Politiques En Côte d’Ivoire: Cas De L’institution Dénommée «Le Médiateur De La République» - Eben-Ezer César Léonce Koffi; Dago Michèle-Ange; Amien Assémien; Josiane Juliette Ehui-Bla; Bah Mahier Jules Michel (European Scientific Journal, ESJ, 2018)
The study of conflict management, especially that relating to mediation, occupies an important place in the advent of conflicts in traditional African environment. In the 1990s, it was introduced gradually into the Ivorian institutions to answer socio-political excesses. However, despite its existence, this institution has faced several oppositions in regards to the aim of the study. This paper focuses on identifying the sociological contours that emerge around the dynamics of mediation in relation to power in the recent conciliatory context. On the basis of direct observations of semi-directive interviews, this research examined the report of the executive on the institution in the conciliatory process. The paper analyzes that the dependence of this institution on the executive power leads to dysfunction of the institution as a result of the reconciliation process.